2018
DOI: 10.2460/ajvr.79.5.505
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic acid synthase-2 gene transfer into the joints of Beagles by use of recombinant adeno-associated viral vectors

Abstract: OBJECTIVE To evaluate gene transfer of recombinant adeno-associated viral (rAAV) vectors with AAV2 or AAV5 capsid and encoding hyaluronic acid (HA) synthase-2 (HAS2) into joints of healthy dogs. ANIMALS 22 purpose-bred Beagles. PROCEDURES Plasmid expression cassettes encoding canine HAS2 (cHAS2) were assessed in vitro for concentration and molecular size of secreted HA. Thereafter, rAAV2-cHAS2 vectors at 3 concentrations and rAAV5-cHAS2 vectors at 1 concentration were each administered intra-articularly into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…It is unknown whether the same immune response would occur intra-articularly. However, the immune response against AAV2 may be related to the inconsistent transduction rate of AAV2 in Kyostio-Moore et al's experiment (29). Immune response regarding AAV2.5 has not been reported to this date.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…It is unknown whether the same immune response would occur intra-articularly. However, the immune response against AAV2 may be related to the inconsistent transduction rate of AAV2 in Kyostio-Moore et al's experiment (29). Immune response regarding AAV2.5 has not been reported to this date.…”
Section: Discussionmentioning
confidence: 90%
“…At the time of writing, our literature search reveals only one study in live dogs describing intra-articular gene therapy using conventional AAV and none using scAAV. That study has evaluated the effect of conventional AAV2 and 5 encoding hyaluronic acid synthase-2 gene in canine sti e joints without a formal screening of AAV serotypes (29). Interestingly, it revealed that conventional AAV5 had consistent gene transfer in a dose-dependent manner, while conventional AAV2 had inconsistent gene transfer with a lack of dose-response effect (29).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that the efficacy and safety of AAV5 for arthritis has been investigated in mouse, 59,60 rat, 61 horse, 62 monkey, 63 and proposed clinical trials (www.clinicaltrials.gov #NCT 02727764 and 03445715), it is reasonable to consider AAV5 for hemophilia. Either synovium (fibroblastlike synoviocytes) 62 or chondrocytes 64 or both 65 can be transduced by AAV5 with different tropisms. 9 In summary, direct supplementation of FVIII by IA delivery in the joint space provided protection against bleeding-induced joint damage, even in the presence of inhibitor antibodies.…”
Section: Table 4 Anti-adeno-associated Virus-neutralizing Antibody In the Plasma And Synovial Fluid In Hemophilia Patientsmentioning
confidence: 99%